Peningkatan Pengelolaan Keuangan melalui Penyusunan Anggaran Kas pada UMKM Tas di Kelurahan Cipamokalan, Kota Bandung - Reni Marlina (Lembaga Pengembangan Kinerja Dosen, 2026)
Small and medium-sized enterprises (SMEs) producing bags play an important role in the regional economy, but still face problems in financial management, particularly cash flow planning. The main problem faced by SME partners producing bags in Cipamokolan Village, Rancasari District, Bandung City, is the lack of comprehensive cash flow planning, which has the potential to cause liquidity problems. This community service activity aims to improve the understanding and skills of bag SME in preparing a simple cash budget and encouraging its sustainable implementation. The methods used include training and mentoring with stages of problem identification, material delivery, cash budget preparation practice, and evaluation. The results of the activity show an increase in partners' understanding of cash planning, their ability to prepare a simple cash budget, and their commitment to implementing a cash budget in their daily business financial management. This activity is expected to improve cash flow control and support the sustainability of bag SME businesses